Guarding Indonesia’s Moderate Islamic Public Sphere? Nahdlatul Ulama’s Intolerant Resistance to Salafi-Wahhabi Institutional Expansion - Mawardi Abdullah; Ahmad Fajar Shodiq (Al'Adalah, 2024)
The rapid institutional expansion of Salafi-Wahhabi groups in Indonesia, challenging the dominance of moderate traditionalist Islam, is important to study because it raises critical questions about tolerance, pluralism, and the quality of democracy in the world's largest Muslim-majority country. Previous research has insufficiently explored the local politics of Nahdlatul Ulama (NU) in managing deliberative public space and the paradox of intolerance within a moderate majority. This study reveals how local NU actors in Jember negotiate resistance to Salafi-Wahhabi preaching and institutional expansion, particularly the Imam Syafi'i Islamic Dirasat College (STDI) in Jember and its affiliated schools. This research employs a qualitative approach involving participant observation and in-depth interviews with NU Jember leaders, cadres, and activists in 2019–2020. Data were analyzed inductively by Habermas's public sphere theory and the concept of Civil Islam. The findings reveal a double paradox: NU's intolerance of takfir and tabdi' practices helps limit exclusivist ideology and protect a moderate public sphere, but its rejection of Salafi educational institutions—which sometimes escalates into confrontation—undermines civil pluralism and contributes to the deconsolidation of local democracy. Future research should adopt a mixed-methods approach to compare regional dynamics and develop inclusive policy frameworks for managing religious public spaces in Muslim-majority democracies.